Protein and carbohydrate intakes alter gut microbial community structure in crickets: a Geometric Framework approach. Issue 8 (4th July 2019) - Ng, Soon Hwee; Stat, Michael; Bunce, Michael; Simpson, Stephen J; Simmons, Leigh W
ABSTRACT: Proteins and carbohydrates have profound impacts on the ecology of gut microbiota, but disentangling the single and interactive effects of different dietary constituents is challenging. Here, we used a multidimensional approach, the Geometric Framework, to study the interactions between nutrition and bacterial abundances with respect to protein and carbohydrate intakes in field cricket, Teleogryllus oceanicus . Our study revealed that species richness decreased as crickets consumed more macronutrients, and species evenness peaked at high intake of protein-rich diets. Sex and protein:carbohydrate (P:C) ratios in diets were the primary factors influencing the gut bacterial community, but most of the microbial operational taxonomic units (OTUs) that were significantly different between males and females were present in low abundance. In contrast, protein intake had a greater influence than carbohydrate consumption on the relative abundances of the core bacterial taxa, as an increase in dietary protein availability could remove the growth constraint imposed by limited nitrogen. Taken together, the use of the Geometric Framework provides a deeper insight into how nutritional intakes influence the relative abundances of gut microbes, and could be a useful tool to integrate the study of gut microbiome and fitness traits in a host. Abstract : The use of the Geometric Framework provides a deeper insight of how specific nutrients influence the relative abundances of gut microbes and impact different aspects of species diversity.